TGFβ1 as a Predictive Biomarker for Collateral Formation Within Ischemic Moyamoya Disease - Chen, Yuanbing; Tang, Miao; Li, Hui; Liu, Hongwei; Wang, Junyu; Huang, Jun (Frontiers in Neurology, 2022)
Objective: Moyamoya disease (MMD) is a unique cerebrovascular occlusive disease characterized by progressive steno-occlusion within the terminal segment of the internal carotid artery. However, good collaterals from an external carotid artery are essential to compensate for the ischemia in moyamoya disease. This study aimed to investigate Transforming growth factor-beta 1 (TGFβ1) in plasma as a potential biomarker for predicting collateral formation in ischemic MMD. Methods: The transcriptome profile downloaded from Gene Expression Omnibus (GEO) was used to analyze the differential expression of genes between the ischemic MMD and the control groups. We prospectively recruited 23 consecutive patients with ischemic MMD that was diagnosed via digital subtraction angiography (DSA). Nine patients with intracranial aneurysms and four healthy people served as controls. The collaterals from the external carotid artery were examined using DSA. We evaluated whether the collateral formation was associated with TGFβ1 in the patients with ischemic MMD. Western blot, RT-qPCR, ELISA, and tube formation assay were used to explore the relationship between TGFβ1 and angiogenesis as well as the potential mechanisms. Results: The mRNA levels of TGFβ1were upregulated in the patients with ischemic MMD. The plasma TGFβ1 levels were higher in the patients with ischemic MMD than in the aneurysm and healthy patients (p<0.05). The collateral formation group has higher levels of serum TGFβ1 than the non-collateral formation group (p<0.05). The levels of vascular endothelial growth factor (VEGF) are positively correlated with TGFβ1 levels in the plasma (R2=0.6115; p<0.0001). TGFβ1 regulates VEGF expression via the activation of the TGFβ pathway within HUVEC cells, as well as TGFβ1 stimulating HUVEC cells to secrete VEGF into the cell culture media. An in vitro assay revealed that TGFβ1 promotes angiogenesis within the endothelial cells. Conclusions: Our findings suggest that TGFβ1 plays a vital role in promoting collateral formation by upregulating VEGF expression in ischemic MMD.